Study skills: A Concept Analysis - SHYAMALA DEVI MANIVANNAN, (International Journal of Pharma and Bio Sciences, 2018)
Success in studies is the output of many factors and the most important is the student himself or herself.Study skills pave ways for success. Understanding the concept of study skills would alert on need for “study skills” to avoid the “prolonged study process” that discourages the stakeholders and the universities. Concept analysis is a method with which the researcher further explores and adds on to the existing meaning and interpretation of the concept under consideration. Study skills of an individual tend to show differences in academic achievements of the students.The present paper aimed at analyzing the concept of, “study skills.”Rodger’s model was utilized to examine the concept “study skills.” Sincere efforts made to 1) define the concept, 2) explain surrogate terms, 3) describe concept attributes, 4) identify the antecedents and consequences of the concept, and 5) discuss a model case of the concept. The main purpose of this concept paper is to explain the concept and its attributes to enhance further understanding and apply in day to day practice. Concept analysis on study skills would help the nursing professionals to get familiarized with different attributes and definitions of the concept .The findings from two previous studies served as the model cases for the present analysis. In depth understanding of “study skills”, help academicians in various ways. Inculcation of good study skills reduces failure rates and helps in preparing academically tuned, “future quality nurses”. Nursing colleges with no or less failure rates find their names in best performers’ list. This paves ways to attract the attention of stakeholders.